Management of Stored Grain Insects, Part III - Sloderbeck, Phillip E.; Subramanyam, Bhadriraju; Bauernfeind, Robert J. (My University, 2005)
This publication helps producers manage stored grain and avoid pest problems.
MF917_2005_06
Keywords: MF917; Insects; Crops; Equipment and structures; MF